Maximum Storm Surge Elevations in the Tuktoyaktuk Region of the Canadian Beaufort Sea - Harper, John R.; Henry, R. Falconer; Stewart, Gordon G. (ARCTIC, 1988)
Storm surges are a significant concern in the siting and design of structures along the Beaufort Sea coast in that the coastal relief is low and the magnitude of surges in this region is large. Coastal storm surge elevations along the southern Canadian Beaufort Sea coast were documented by surveying log debris lines in the Kugmallit Bay/Tuktoyaktuk region. Careful attention to sire selection and survey technique resulted in estimated errors in surge elevation measurements of less than ±0.3 m. The data indicate a local surge maximum has occurred at Tuktoyaktuk at approximately 2.4 m above mean sea level (MSL); lower maximum surge elevations (2 m above MSL) were documented to the north and west of Tuktoyaktuk. There is no evidence that higher surges have occurred during the last 100 years. A surge that occurred in August 1986 measured approximately 1.6 m above MSL at Tuktoyaktuk and decreased to approximately 1.4 m above MSL 20 km to the north and west of Tuktoyaktuk. These surge elevation data provide a basis for the calibration of numerical models of surge and can be used directly in siting and design analysis of coastal structures.Key words: Beaufort Sea coast, storm surges, Kugmallit Bay, Tuktoyaktuk Mots clés: côte de la mer de Beaufort, houle des tempêtes, baie de Kugmallit, Tuktoyaktuk